SOSIALISASI MARKETING MIX UNTUK PENINGKATAN PENJUALAN UMKM DI DESA TANJUNG PAUH MUDIK KEC. DANAU KERINCI BARAT - Ade Taufan; Riri Wulandari; Angra Melina; Hayati; Dian Andriyani (AbdiMasya | Hira Institute, 2024)
The marketing mix socialization service to increase UMKM sales was carried out against the background of the lack of socialization carried out by UMKM actors in Tanjung Pauh Mudik village, West Lake Kerinci District, while the method used in implementing this service was that the service team used lecture, discussion and question methods. answer, after the presenter has delivered the material, the participants can ask directly which things are not clear, and the result of carrying out this service is that almost 80% of UMKM in Tanjung Pauh Mudik Village understand the marketing mix